Oral and Intestinal Microbiocenosis in Children with Erosive and Ulcerative Oral Diseases - Kozhonazarova, Gulsara; Uzakov, Orozali; Alymbaev, Erkin; Sulaymanov, Shayirbek; Malevannaya, Valeria; Terekhova, Oksana; Ongoyeva, Bermet; Abdurakhmanov A.A., Almaz; Umashev, Samat; Akmatova, Altynai; Chubakova, Baktygul; Melisbekova, Aliya; et al. (ENT Updates, 2025)
Erosive and ulcerative oral diseases, such as recurrent aphthous stomatitis and herpetiform ulcers, are common in children and significantly affect their quality of life. This observational study investigated the relationship between oral and intestinal microbiocenosis and the onset of these conditions in 648 children aged 1–16 years. Microbiological examination revealed dysbiotic changes in the oral and gut microbiota of affected children compared to controls, with a significant decrease in beneficial commensal bacteria, particularly Bifidobacterium and Lactobacillus species, and an increase in opportunistic pathogens, such as Staphylococcus and Candida spp. The reduction in Bifidobacteria and Lactobacilli in both oral and stool samples supports the concept of a gut-oral microbial axis in the manifestation of these diseases. These findings suggest that systemic factors, such as intestinal microbial imbalance, may contribute to the development of recurrent oral lesions in children. Incorporating microbiota analysis into the diagnostic process and considering targeted treatments, such as probiotics and dietary adjustments, could improve clinical outcomes. This study emphasizes the importance of a multidisciplinary approach involving collaboration among ENT specialists, pediatric dentists, gastroenterologists, and microbiologists to comprehensively evaluate and manage these conditions in children. Further research is needed to elucidate the causal relationships between microbial shifts and disease flares and to develop personalized microbiota-based interventions for pediatric patients with erosive and ulcerative oral diseases.